Improving Vocabulary Mastery through Direct Instruction - Fitriani; Abin, Rais; Karimuddin; Zakaria; Astiantih, Susi; Suryadi, Ray (Research Horizon, 2025)
The low mastery of students' skills in learning English and the limited application of explicit learning strategies such as DI in English as a Foreign Language (EFL) class in Indonesia. This study aims to determine the effectiveness of the Direct Teaching (DI) strategy in improving the mastery of understanding of grade VII students at State Junior High School 3 Tanggetada. The method used in this study is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementing actions, observation, and reflection. The research subjects were 18 students who were selected purposively based on their low mastery of understanding. Data collection techniques include insight tests, student and teacher activity observation sheets, and field notes. Data analysis was carried out descriptively quantitatively and qualitatively to assess the development of student learning outcomes and behavior during the learning process. The results of the study indicate that the application of the Direct Teaching strategy can improve students' mastery of understanding and encourage active involvement in the learning process. Students become more confident, motivated, and able to understand understanding in a more structured way.